Sejam as funções definidas por f (x)= 2x + 3 e g) (x)= 5x + 5, Determine.
A) f(1)+ f(7)=
B) f(-1) + f(3) =
Respostas
respondido por:
0
Letra "A"
F(1) = 2.(1) +3 = 5
F(7) = 2.(7) + 3 = 14 + 3 = 17
F( 1 ) + F ( 7 ) = 5 + 17 = 22
Letra "B"
F(-1) = 2(-1) + 3 = -2 + 3 = 1
F(3) = 2.(3) + 3 = 6 + 3 = 9
F ( -1 ) + F ( 3 ) = 1 + 9 = 10
F(1) = 2.(1) +3 = 5
F(7) = 2.(7) + 3 = 14 + 3 = 17
F( 1 ) + F ( 7 ) = 5 + 17 = 22
Letra "B"
F(-1) = 2(-1) + 3 = -2 + 3 = 1
F(3) = 2.(3) + 3 = 6 + 3 = 9
F ( -1 ) + F ( 3 ) = 1 + 9 = 10
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás